Could a Mediterranean Diet Modulate Alzheimer’s Disease Progression? The Role of Gut Microbiota and Metabolite Signatures in Neurodegeneration - Alice N. Mafe; Dietrich Büsselberg (Foods)
Neurodegenerative disorders such as Alzheimer’s disease (AD), the most common form of dementia, represent a growing global health crisis, yet current treatment strategies remain primarily palliative. Recent studies have shown that neurodegeneration through complex interactions within the gut–brain axis largely depends on the gut microbiota and its metabolites. This review explores the intricate molecular mechanisms linking gut microbiota dysbiosis to cognitive decline, emphasizing the impact of microbial metabolites, including short-chain fatty acids (SCFAs), bile acids, and tryptophan metabolites, on neuroinflammation, blood–brain barrier (BBB) integrity, and amyloid-β and tau pathology. The paper highlights major microbiome signatures associated with Alzheimer’s disease, detailing their metabolic pathways and inflammatory crosstalk. Dietary interventions have shown promise in modulating gut microbiota composition, potentially mitigating neurodegenerative processes. This review critically examines the influence of dietary patterns, such as the Mediterranean and Western diets, on microbiota-mediated neuroprotection. Bioactive compounds like prebiotics, omega-3 fatty acids, and polyphenols exhibit neuroprotective effects by modulating gut microbiota and reducing neuroinflammation. Furthermore, it discusses emerging microbiome-based therapeutic strategies, including probiotics, prebiotics, postbiotics, and fecal microbiota transplantation (FMT), as potential interventions for slowing Alzheimer’s progression. Despite these advances, several knowledge gaps remain, including interindividual variability in microbiome responses to dietary interventions and the need for large-scale, longitudinal studies. The study proposes an integrative, precision medicine approach, incorporating microbiome science into Alzheimer’s treatment paradigms. Ultimately, cognizance of the gut–brain axis at a mechanistic level could unlock novel therapeutic avenues, offering a non-invasive, diet-based strategy for managing neurodegeneration and improving cognitive health.